"A little on the heavy side": a qualitative analysis of parents' and grandparents' perceptions of preschoolers' body weights. Issue 12 (11th December 2014) - Eli, Karin; Howell, Kyndal; Fisher, Philip A; Nowicka, Paulina
Abstract : Objectives: Parents' difficulties in perceiving children's weight status accurately pose a barrier for family-based obesity interventions; however, the factors underlying weight misinterpretation still need to be identified. This study's objective was to examine parents and grandparents' perceptions of preschoolers' body sizes. Interview questions also explored perceptions of parental responsibility for childhood obesity and appropriate contexts in which to discuss preschoolers' weights. Design: Semistructured interviews, which were videotaped, transcribed and analysed qualitatively. Setting: Eugene and the Springfield metropolitan area, Oregon, USA Participants: Families of children aged 3–5 years were recruited in February—May 2011 through advertisements about the study, published in the job seekers' sections of a classified website (Craigslist) and in a local newspaper. 49 participants (22 parents and 27 grandparents, 70% women, 60% with overweight/obesity) from 16 low-income families of children aged 3–5 years (50% girls, 56% with overweight/obesity) were interviewed. Results: There are important gaps between clinical definitions and lay perceptions of childhood obesity. While parents and grandparents were aware of their preschoolers' growth chart percentiles, these measures did not translate into recognition of children's overweight or obesity. The participants spoke of obesity as a problem that may affect the children in the future, but not at present. Participants identified childhood obesity as being transmitted from one generation to the next, and stigmatised it as resulting from 'lazy' parenting. Parents and grandparents avoided discussing the children's weights with each other and with the children themselves. Conclusions: The results suggest that clinicians should clearly communicate with parents and grandparents about the meaning and appearance of obesity in early childhood, as well as counteract the social stigma attached to obesity, in order to improve the effectiveness of family-based interventions to manage obesity in early childhood.